Carbazolic Conjugated Microporous Polymers for Photocatalytic Organic Transformations. Issue 8 (12th March 2023) - Zhang, Weijie; Shu, Caihua; Cui, Haishuai; Wan, Quan; Au, Chak‐Tong; Yi, Bing; Yang, Hai
Abstract: Heterogeneous photocatalysis have been deemed as a versatile and colorful platform for exploring efficient transformation systems. Henceforth, the design of photocatalysts underpins a wide range of research interests. By virtue of synthetic versatility, stability, non‐toxicity, purely organic properties, tunable semiconductive structures, and remarkable visible‐light absorbance, conjugated microporous polymers (CMPs) have emerged as an attractive new class of semiconductor materials that show great potential for tackling important energy and environmental challenges. Over the past decade, immense efforts have been devoted toward the construction of CMPs‐based photocatalysts for versatile photocatalytic transformations. This review aims to summarize the latest representative advances in the field of carbazolic CMPs, focusing on various design strategies for the construction of tailor‐made skeletons that have direct impact on their charge dynamics and thus photocatalytic performances, especially on their specific photocatalytic efficiency for organic transformations. Scrutinizing the photocatalytic features and elucidating the related design principles, it is fully described how structure modification of polycarbazoles could have an effect on optical properties, and thus on photocatalytic performance. Furthermore, the bottlenecks that need to be addressed, and the future research directions of CMPs are identified in the area of photocatalysis. Abstract : Carbazolic conjugated microporous polymers have moved to the forefront of materials science, providing a powerful platform for catalysis due to their unprecedented combination of excellent stability. This review primarily focuses on the associated structural design principles of how the structure modification of polycarbazoles could affect the optical property, photogenerated charge separation and transfer, and thus the targeted photocatalytic conversions.